Study of genital dermatoses in pregnant females attending a tertiary care hospital - Sivanu, Seeniammal; Babu, Maalik; Savadamoorthi, Soundharyaa Moorthi (International Journal of Research in Dermatology, 2019)
Background: Sexually transmitted infections (STI) prevalence in pregnancy is high and causes severe risk of transmission to the newborn. Usually they are asymptomatic and underdiagnosed. Most common STI’s are VVC, HPV, genital herpes, HIV, etc. Methods: A hospital-based cross-sectional study was done for a period of one year (September 2017- August 2018) and 31 pregnant genital dermatoses were encountered. Results: Among 31, infective etiology was seen in 15 cases (48%), non-infective etiology was seen in 3 cases (10%) and no STI’s were seen in 13 patients (42%). Vulvovaginal candidiasis was most common among pregnant females in 9 patients (60%) followed by genital warts in 3 patients (20%) followed by molluscum contagiosum, herpes genitalis and oral candidiasis in one patient (7%) respectively among infective etiology. Non-infective causes include vulval lymphangiectasia, epidermoid cyst and vascular swelling in one patient respectively (33.3%). Conclusions: Screening of antenatal cases is more important to prevent complications.